TECHNOLOGIES TO INCREASE THE PHYSICAL FITNESS OF YOUNG PLAYERS (International journal of artificial intelligence, 2025)
This article will analyze the main methods of improving the physical fitness of players, modern technologies and training methodologies. Fitness focuses on developing players ' strength, stamina, speed, and flexibility, which is important in increasing their effectiveness in the game. The article will also show the importance of innovative technologies used in the training of young players, heart rate monitoring, GPS trackers and virtual reality tools. Combined with nutrition, recovery, and coaching approaches, fitness is the foundation for players ' long-term success in the sport.